A systematic genetic analysis and visualization of phenotypic heterogeneity among orofacial cleft GWAS signals. Issue 6 (6th June 2019) - Carlson, Jenna C.; Anand, Deepti; Butali, Azeez; Buxo, Carmen J.; Christensen, Kaare; Deleyiannis, Frederic; Hecht, Jacqueline T.; Moreno, Lina M.; Orioli, Ieda M.; Padilla, Carmencita; Shaffer, John R.; Vieira, Alexandre R.; et al.
Abstract: Phenotypic heterogeneity is a hallmark of complex traits, and genetic studies of such traits may focus on them as a single diagnostic entity or by analyzing specific components. For example, in orofacial clefting (OFC), three subtypes—cleft lip (CL), cleft lip and palate (CLP), and cleft palate (CP) have been studied separately and in combination. To further dissect the genetic architecture of OFCs and how a given associated locus may be contributing to distinct subtypes of a trait we developed a framework for quantifying and interpreting evidence of subtype‐specific or shared genetic effects in complex traits. We applied this technique to create a "cleft map" of the association of 30 genetic loci with three OFC subtypes. In addition to new associations, we found loci with subtype‐specific effects (e.g., GRHL3 [CP], WNT5A [CLP]), as well as loci associated with two or all three subtypes. We cross‐referenced these results with mouse craniofacial gene expression datasets, which identified additional promising candidate genes. However, we found no strong correlation between OFC subtypes and expression patterns. In aggregate, the cleft map revealed that neither subtype‐specific nor shared genetic effects operate in isolation in OFC architecture. Our approach can be easily applied to any complex trait with distinct phenotypic subgroups.